Induction of Somatic Embryogenesis through Overexpression of ATRKD4 Genes in Phalaenopsis “Sogo Vivien” - Exsyupransia Mursyanti; Aziz Purwantoro; Sukarti Moeljopawiro; Endang Semiarti (Universitas Gadjah Mada, 2015)
Phalaenopsis “Sogo Vivien “is a mini orchid hybrid with beautiful flowers and numerous inflorescences.Mass propagation of this orchid is needed to meet the market demand. Objective of this research was toinduce somatic embryogenesis of P.”Sogo Vivien” through insertion of AtRKD4 gene into orchid. T-DNAcontaining 35S::GAL4::AtRKD4::GR was inserted into 16-22 days after sowing orchid protocorms mediated byAgrobacterium tumefaciens EHA 105. Activation of the AtRKD4 gene was induced by glucocorticoid inductionsystem, using 15μM Dexamethasone (Dex). The results showed that 34 out of 2,648 orchid embryos developedinto protocorms on hygromycin selection medium, whereas only 4 out of 2,897 non-transformant protocormsdeveloped from embryos. A 500 bp of HPT genes was amplified from transformant candidates using specificprimers for HPT (HygF1 and HygR1) and 380 bp was amplified using specific primers for AtRKD4 (AtRKD4F1 and AtRKD4 R1), indicated that transgenes have been integrated into orchid genomes. Finally, 17 plantletswere positively carrying AtRKD4 and HPT genes, the efficiency of transformation was 0.63 %. Somatic embryoswere also emerged from leaf explants of transformant on hormone-free NP medium and became normalplantlets. It is probably due to the high activity of AtRKD4 genes in orchids